Post-polymerization 'click' end-capping of polyglyoxylate self-immolative polymers. Issue 47 (26th October 2021) - Maschmeyer, Peter G.; Liang, Xiaoli; Hung, Allison; Ahmadzai, Oksana; Kenny, Annmaree L.; Luong, Yuan C.; Forder, Timothy N.; Zeng, Haoxiang; Gillies, Elizabeth R.; Roberts, Derrick A.
Abstract : Post-polymerization CuAAC reactions are used to 'click' stimuli-cleavable triazole end-caps onto self-immolative poly(ethyl glyoxylate). Abstract : Post-polymerization modification is a powerful tool for expanding the functionality and tuning the properties of self-immolative polymers (SIPs), typically through reactions of the polymer repeat units. Herein, we investigate the use of post-polymerization 'click' reactions to attach stimuli-responsive end-caps to poly(ethyl glyoxylate) (PEtG) SIPs. Two classes of alkyne-terminated polymers were synthesized, with the alkyne attached to the PEtG either by an acetal or carbonate bridge. These PEtGs were treated with azide-functionalized self-immolative linker precursors via the copper(i ) catalyzed azide–alkyne cycloaddition reaction to afford PEtGs end-capped with cleavable self-immolative triazole (SIT) linkers. Our results demonstrate that degradation of the PEtGs can be initiated by cleavage of the SIT end-caps, and that successful cleavage depends strongly on the moiety that connects the SIT linker to the PEtG backbone. Through depolymerization studies on the polymers and a series of small molecule model compounds, we examined in detail the mechanistic features of this system. Additionally, we demonstrate that this modular chemistry is versatile for introducing different stimuli-responsive end-caps to a single pre-synthesized PEtG.